326 Lifetime prevalence and one-year incidence of sport-related concussion in adolescents. (3rd March 2020) - McCallum, Jocelyn; Emery, Carolyn; Eliason, Paul H; Schneider, Kathryn; Black, Amanda M
Abstract : Background: Understanding the burden of concussion among youth is important to quantify the effectiveness of community-based concussion prevention strategies. Objective: To determine the lifetime prevalence and one-year incidence of sport-related concussion among male and female high school students (ages 14–19 years) in Alberta, Canada. Design: Cross-sectional survey. Setting: High schools (Alberta, Canada). Participants : High school students (n=2029; 958 male, 1048 female, 23 identified as 'other'; ages 14–19 years) from 24 schools. Assessment of Risk Factors : High school students completed a web-based survey during class (October 2018 – March 2019). Students identified the top three sports for participation in the past year. Main outcome measurements: Self-reported lifetime prevalence and one-year incidence of sport-related concussion were described by sex and sport with 95% confidence intervals (CI) adjusted for cluster by school. Results: Most high school students (1763/2029, 86.69%) reported participating in a sport/recreational activity in the past year. Of the 1, 971 students (97.14%) answering the question about lifetime concussion history, 264/923 males [28.60% (95% CI, 21.97–36.31)], 227/1027 females [22.10% (95% CI, 17.96–26.89)], and 3/21 'other' students [14.29% (95% CI, 2.22–55.05)] reported one concussion or more. 131/923 males [14.19% (95% CI, 10.28–19.27)], 99/1027 females [9.64% (95% CI, 7.49–12.33)], and 1/21 'other' students [4.76% (95% CI, 0.46–35.28)] reported at least one concussion in the past year. For males, hockey [32/186, [Incidence Proportion(IP):17.20/100 students/year (95% CI, 12.48–23.23)], lacrosse [4/29, IP: 13.79/100 students/year (95% CI, 5.27–31.52)], and rugby [8/61, IP: 13.11/100 students/year (95% CI, 6.02–26.24)] had the highest rates of concussion. For females, ringette [4/21, IP: 19.05/100 students/year (95% CI, 9.92–33.46)], rugby [9/58, IP: 15.52/100 students/year (95% CI, 8.04–27.84)], and wrestling [3/25, IP: 12.00/100 students/year (95% CI, 3.68–32.76)] had the highest rates. Conclusions: 1 in 4 high school students report one or more sport-related concussions in their lifetime, and 1 in 9 students reported one or more concussions in the past year. Prevention strategies aimed at reducing concussion burden are crucial.